Entre excessos e ausências: práticas culturais de professores universitários que atuam em cursos de Pedagogia - Renata Nayara Ribeiro (2014)
The research aims to analyze the cultural practice of Pedagogy professors who work in Belo Horizontes institutions, one private and other public, with the intent on comprehending how this professors relate with their cultural practice. We believe in the importance of knowing more about this reality since we know little about the professors cultural practice. By a large way of understanding cultural practices, we chose an approach that enables a wide notion of culture, thus contemplating all the complexity of the cultural practices rupturing the hierarchical view of the cultural practices as well as the passivity of the receptor. Therefore we used as a base the earliest studies of the cultural history, especially the ones among the French Historiography, for example Chartier, Certeau e Bourdieu. We understand that each of the authors bring potential for the cultural practice study . The research was held in two Universities of Belo Horizonte, one private and the other public, to show different samples of different Pedagoy professors working conditions. The data was gathered in two stages, the first was a survey that all the professors, from both Pedagogy institutions, had to fill themselves. The final sample is made by 60 surveys, the data was tabbed and analyzed according to frequency, crossed between variants and organized in tables and graphs through the statistical analysis program Statiscal Package for Social Sciences (IBM SPSS Statistics 20). After the data analysis, a second survey was held by interviewing of seven selected professors in order complement the information that wasnt acquire by the surveys. From the categorization and data analysis we had access to a prospect of the professors cultural practice, that showed a variety of practices. Among the results we could notice that professors have different relations with their cultural practice, being noticeable the importance given to profession and family aspects. We found a considerable preference by domestic practices and the strong connection between friends and Family besides working practices that end up invading the domestic environment. Can it be said that the new /current college professor, has got a simple domestic life, likes to work and to organize educational projects , shows a considerable effort to joint work and family, the aspects that take most of his/her time.